Crack Self-Healing of Cement Mortar Containing Ureolytic Bacteria Immobilized in Artificial Functional Carrier under Different Exposure Environments - Mian Luo; Ye Liu; Xu Li; Junjie Dai (Buildings, 2022)
The ureolytic bacteria and nutrients were immobilized in the artificial functional carrier (AFC) and the self-healing cement mortar, based on the AFC-encapsulated bacteria, was prepared for this paper. The crack self-healing effect of mortars with and without bacteria under different exposure environments (standard curing, dry–wet cycle curing, and water curing) was investigated by the visual observation of surface and internal cracks, water permeability tests, and mechanical performance recovery. In addition, the internal healing products of the cracks were observed using the metallographic microscope. The results show that the mortar specimens containing ureolytic bacteria immobilized in artificial functional carrier have a higher crack area repair ratio, and better water tightness regain and recovery ratio of flexural strength compared with the control mortars under the same exposure environment. The self-healing effect of mortar cracks with and without bacteria is obviously affected by the exposure environments. The self-healing effect of the cracks are the best when the mortar specimens are cured in water, followed by dry–wet cycle curing, and the self-healing effect of the cracks is the worst in standard curing, indicating that the presence of water is necessary for crack self-healing. The mortar specimens with bacteria generate more repair products in the surface and interior of the cracks to greatly improve the self-repair ability of the specimens, which promotes the recovery of water tightness and mechanical performance.